A critique of creative Shariah compliance in the Islamic finance industry - Alkhamees, Ahmad (Brill's Arab and Islamic laws series, 2017)
This book significantly contributes to the sphere of Islamic finance in three main ways. First, it critically appraises justifications of creative Shari?ah compliance practises. Second, it examines how Shari?ah supervisory board (SSB) governance practises, and the inconsistent fatwas issued by SSBs, contribute to the issue of creative Shari?ah compliance.